Analysis of Gross Motor Development of Children Aged 4-5 Years through the Implementation of the Smart Basket Game - Rohfirsta, Fulka; Zulfahmi, Muhammad Nofan (EduBasic Journal: Jurnal Pendidikan Dasar, 2024)
To control body movements, the central nervous system, peripheral nerves, and large muscles are all involved in gross motor development in early childhood. The development of children's gross motor skills is greatly influenced by both genetic factors and environmental stimuli. This study, therefore, employed qualitative research methods to examine how the Smart Basket game affected the gross motor development of children between the ages of 4 and 5 at the Play Group of Jelita Krapyak. This game was designed for the introduction of numbers to sports. Documentation, interviews, and observation were some of the data collection methods used. The primary findings revealed that the Smart Basket game research successfully improved children's gross motor development. This suggests that children's gross motor development can benefit from an approach that combines physical activity with number recognition. Hence, it can be deduced that the implementation of this game holds promise for enhancing early childhood individuals' gross motor skills, social skills, and understanding of numerical concepts in early childhood. This game also has easy procedures for implementing and maintaining the properties. The significance of incorporating physical activity and the acquisition of numerical concepts within the context of early childhood education is the implication of this study.